APPLICATIONS OF NANOBREEDING FOR THE ENHANCEMENT OF FOOD SECURITY (FULafia Journal of Science and Technology, 2024)
As the world population continues to expand and environmental challenges escalate, ensuring food security has become an urgent global concern. This paper explores the potential of nanotechnology in addressing these challenges, particularly in the field of crop improvement. Nanobreeding, which utilizes nanotechnological tools and techniques, presents a promising approach to enhance crop production and quality while minimizing environmental impact. Precision agriculture benefits greatly from nanosensors, which provide real-time data on soil moisture, nutrient levels, and pest infestations. Nanotechnology also offers innovative solutions in pest management through the development of nanopesticides. These nanopesticides enable targeted delivery of active ingredients to specific pests or plant structures, reducing off-target effects and environmental contamination. Addressing the challenges of low nutrient use efficiency and environmental pollution associated with conventional fertilizers, nano-fertilizers emerge as a viable solution. Nanotechnology in agriculture presents innovative solutions to enhance crop production, improve resource efficiency, and minimize environmental impact. By harnessing the potential of nanotechnology, these can contribute to global food security, meet the growing demand for food, and maintain sustainable living standards. Continuous research and development in this field are essential in securing our future food supply and building a resilient agricultural system.
Keywords: Nanobreeding; food security; nanosensor; nanofertilizer; nanopesticide